Alain Altinoglu conducts Khachaturian, Petrossian, Komitas, and Mozart - Khachaturi͡an, Aram 1903-1978; Petrossian, Michel 1973-; Mozart, Wolfgang Amadeus 1756-1791 (Wahoo Productions - UGAB, 2015)
On April 21, 2015, the French-Armenian conductor Alain Altinoglu led the Armenian World Orchestra (AWO) in a memorial concert to mark the 100th anniversary of the Armenian Genocide. The evening celebrated Armenian heritage and honored the Genocide's victims with a moving program of traditional Armenian and Western classical music that included a world premiere by French-Armenian composer Michel Petrossian. Accomplished artists of Armenian origins came from all over the globe to form the orchestra for this concert organized by the Armenian General Benevolent Union France (AGBU France). They began with Aram Khachaturian's Masquerade Suite, a spellbinding work that originated as incidental music for a 1941 play by Russian playwright Mikhail Lermontov. Next came arrangements for orchestra of haunting traditional Armenian folk tunes compiled by Komitas, an Armenian priest and pioneer ethnomusicologist who lived through the Genocide. The premiere of Petrossian's Ciel à vif, for choir, orchestra, and a trio concertante of piano, violin, and cello followed. A sort of panorama of Armenian culture, the work's diverse references include traditional Armenian song, biblical texts, and even dialogue from a film by Jean-Luc Godard. Mozart's Requiem concluded this contemplative and emotional evening of remembrance
Keywords: Suites (Orchestre); Churs profanes (Voix mixtes) acc. d'orchestre; Requiem; Choruses, Secular (Mixed voices) with orchestra; Folk music; Requiems; Suites (Orchestra); Shvi and Svirala with orchestra; Folk music -- Armenia; Armenia; Webcast; Concert films; Internet videos; Concerts filmés; Vidéos sur Internet